Extrarenal angiomyolipoma of paratesticular and subcutaneous region: a report of two cases at rare sites - Rajeshwari, B; Salapathi, Shanmugam; Ghosh, Mitra (Annals of Pathology and Laboratory Medicine, 2020)
Angiomyolipomas are benign mesenchymal neoplasms consisting of variable proportion of mature adipose tissue, thick walled blood vessels and smooth muscle bundles. Although initially thought to be hamartomas, now they are considered to be tumours derived from perivascular epithelioid cells(PEC) hence grouped under a family of tumours known as PEComas. The tumour mainly involves kidneys and are more common in patients with tuberous sclerosis. However extrerenal angiomyolipomas are being increasingly described with liver and retroperitoneum being the most common extrarenal sites. Other sites described include nasal cavity, oral cavity, colon, lung, skin, adrenal glands and bladder. Here we report two cases of extrarenal angiomyolipomas of paratesticular and subcutaneous region, the rarely described sites in the literature. There were no clinical signs of tuberous sclerosis in both cases. Although literature suggests that these tumours show immunohistochemical coexpression of myogenic and melanocytic markers with consistent expression of HMB-45, our both cases were negative for HMB-45. However both cases showed classical triphasic morphology. Although rare, it is important to screen these patients for tuberous sclerosis associated lesions for early diagnosis.